Effect of Storage on Seed Viability in Some Leguminous Taxa - Sahai, Kanak (Indian Forester, 1999)
Effect of storage on seed viability of 26 leguminous taxa at different temperatures was studied continuously for seven years (1990-1996). Average of the results oftetrazolium test and seed germinability was expressed as seed viability. It varied from species to species and variety to variety even under the same storage conditions.